Utility of cell population data to detect myelodysplastic neoplasms in routine laboratory analysis. - Gunson, Hanna (Australian Journal of Medical Science, 2025)
Myelodysplastic neoplasms (MDN) are a heterogeneous group of clonal disorders characterised by abnormal production and proliferation of cells within the myeloid cell linage. MDN is more commonly diagnosed in older people and the clinical manifestations vary depending on the severity and specific type of the disorder. The disease is often detected during routine blood film examination, triggered by the laboratory review criteria which should be based on the International Consensus group suggested criteria (Barnes et al 2005). While MDN may be slow to progress, progression to acute myeloid leukaemia occurs in approximately 30% of cases (Bejar and Steensma 2014). Early detection of MDN, through triggers outside the Consensus guidelines, may facilitate timely treatment initiation and improve patient outcomes.